2015
DOI: 10.1103/physrevc.91.054326
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of quadrupole collectivity inN=80isotones toward theZ=64subshell gap: TheB(E2;

Abstract: It was shown that the evolution of the B(E2; 2 + 1 → 0 + 1 ) values in N = 80 isotones from Te to Nd is affected by the underlying subshell structure. This manifests itself in the observation of the local suppression of the B(E2) value at Z = 58 with respect to the neighboring nuclei 136 Ba and 140 Nd. To investigate this shell sensitivity toward the Z = 64 subshell gap, the B(E2; 2 + 1 → 0 + 1 ) value of the unstable nucleus 142 Sm was measured utilizing the projectile Coulomb excitation technique. The radioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The latter has received much attention from both experimentalists and theorists. By 1 → 0 + 1 ) values for 134−138 Sm [29], 140 Sm (present work), and the value for 142 Sm [40] compared to theoretical calculations using the general Bohr Hamiltonian (BH) based on a Nilsson potential [41], the interacting boson approximation (IBA) [19], a simple rotational model based on a deformed Woods-Saxon potential (WS) [14], and the 5DCH calculations based on the Gogny D1S interaction from the present work.…”
Section: Discussionmentioning
confidence: 98%
“…The latter has received much attention from both experimentalists and theorists. By 1 → 0 + 1 ) values for 134−138 Sm [29], 140 Sm (present work), and the value for 142 Sm [40] compared to theoretical calculations using the general Bohr Hamiltonian (BH) based on a Nilsson potential [41], the interacting boson approximation (IBA) [19], a simple rotational model based on a deformed Woods-Saxon potential (WS) [14], and the 5DCH calculations based on the Gogny D1S interaction from the present work.…”
Section: Discussionmentioning
confidence: 98%
“…Bauer et al [44] and Stegmann et al [45] Nd has the expected dependence on p n N N (whereas a dip is observed [92] for 58 138 Ce corresponding to the p ( ) g 7 2 subshell closure at Z=58), the value for 62 142 Sm deviates significantly from the p n N N behavior, reflecting the impact of the p ( ) g d 1 2…”
Section: Evolution Of Quadrupole Collectivity Away From Closed Shellsmentioning
confidence: 89%
“…Bauer et al [44] and Stegmann et al [45] investigated the evolution of quadrupole collectivity for the N=80 isotones, by measuring the  Rn. They observed that contributions from collective excitations are present in these nuclei when moving away from the N=126 closed shell, although they have been proposed to lie in, or at the boundary of the region where the seniority scheme should persist.…”
Section: Evolution Of Quadrupole Collectivity Away From Closed Shellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of B(E2) values for transitions in the quasirotational bands on top of the 10 + 1 and 10 + 2 states in 138 Nd (a) and 140 Sm (b) with B(E2) values of transitions in the ground-state bands of the respective (Z − 2) and (N + 2) cores. The B(E2) values for 136 Ce [33], 138 Nd (present work), 140 Nd [41], 140 Sm[15], and 142 Sm[43] are given in Weisskopf units, and the widths of the transitions are proportional to the corresponding B(E2) values.…”
mentioning
confidence: 99%